Community-Associated Methicillin-Resistant Staphylococcus Aureus in the Oral Cavity - Enass Almkhadhree; Kawther Alqaseer; Ohood Aqeed Radhi; Baleegh A. Kadhim; Mansour A. Falah; Hawraa Al-Yasseree; Wijdan Dhaidan Shnain; Intisar Jameel Albandar; Esraa Shaker (Kufa Journal for Nursing Sciences)
The oral cavity is habitat to a wide variety of commensal flora, which may act as a reservoir of factors that influence drug resistance. Bacteria in the oral cavity create biofilms, which makes it easier for horizontal gene transfer to result in the accumulation of antibiotic resistance genes. Methicillin-resistant Staphylococcus aureus (MRSA) carriage rates in the oral cavity are high, according to recent studies. The widespread use of antibiotic prophylaxis among at-risk dental procedure applicants may facilitate MRSA establishment in the mouth.  These modifications in the epidemiology of MRSA have significant ramifications for clinical practice, methodological approaches to MRSA carriage studies, and MRSA prevention efforts.